The Monad : the hegemony of personality - Eric Williams and the post independence imagination of Trinidad, 1956-1981 - Ramcharitar, Raymond (2012)
Examines the hegemony of Dr. Eric Williams, former Prime Minister of Trinidad of Tobago, from the perspective of the monad - the phenomenon of individuals who, coming to power at crucial moments, are able to impose an extraordinary amount of authority over the citizens of the small states over which they have acquired control.